2023
DOI: 10.1097/mou.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal vs. transrectal biopsy to reduce postinterventional sepsis

Abstract: Purpose of reviewProstate biopsy is commonly performed in men suspected to have prostate cancer. It has traditionally been performed using a transrectal approach, but transperineal prostate biopsy has been increasingly adopted in part because of its lower associated infectious risk. We review recent studies evaluating the rate of potentially life-threatening post-biopsy sepsis and potential preventive strategies.Recent findingsAfter performing a comprehensive literature search, 926 records were screened and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, its most important advantage is that it has lower post-biopsy ICs compared to TRUS-PB. A recent meta-analysis found that TP-PB had a lower risk of sepsis (0–1%) than TRUS-PB (0.4–9.8%) [21]. Another meta-analysis demonstrated a similar result that TP-PB was associated with significantly reduced ICs, 3.2% versus 5.6% (OR = 0.55; 95% CI, 0.33–0.92) compared to TRUS-PB [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, its most important advantage is that it has lower post-biopsy ICs compared to TRUS-PB. A recent meta-analysis found that TP-PB had a lower risk of sepsis (0–1%) than TRUS-PB (0.4–9.8%) [21]. Another meta-analysis demonstrated a similar result that TP-PB was associated with significantly reduced ICs, 3.2% versus 5.6% (OR = 0.55; 95% CI, 0.33–0.92) compared to TRUS-PB [22].…”
Section: Discussionmentioning
confidence: 99%